Raising Competitiveness of Russian Universities on the Global Scene: Problems and Their Solution - V. I. Grishin; D. A. Shtykhno; E. V. Shubenkova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article shows key ways of resolving the problem facing the system of higher education in Russia, i.e. raising competitiveness in global education space. It analyzes the promotion of Russian universities in leading international ratings, special attention is paid to participation of universities that are not included in the Project 5-100, for instance the Russian Plekhanov University of Economics, to the necessity of extending the number of participants, their rotation and toughening requirements to project participants. The authors study problems facing universities in international promotion: the need to change the approach to students' teaching on the basis of advanced technologies, the development of personnel potential at the expense of training young academic and pedagogical staff, their retaining and attraction of foreign scientists and lecturers, talented overseas students, development of university science, raising the quality and demand for findings of Russian universities' research, increasing publication activity of academic and pedagogical staff and improving the quality of their publications. The authors show that in order to resolve these and many other problems participation of production and business companies is essential and they also characterize the most effective ways of interaction between business and universities.